Strategi Media Sosial Lembaga Alkitab Indonesia (LAI) sebagai Elemen Komunikasi Pemasaran Terpadu - Winarko, Hilarius Bambang (Universitas Bunda Mulia, 2023)
It is felt that the solution to digital or online marketing communication problems at the Indonesian Bible Institute (LAI) still faces obstacle. The obstacle currently encountered is due to a gap in strategic concept even though the mastery and purchasing power of technology implementation has been carried out, one of which is in terms of implementing the use of communication via social media platforms. Currently there is little academic research and theory that discusses the use of social media for non-profit humanitarian organizations, such as the Indonesian Bible Institute (LAI). LAI is a member of the United Bible Societies, an organization that oversees hundreds of national Bible Societies which are active in translation, production and distribution of the Bible throughout the world, including in Indonesia. Currently the LAI social media team has several social media, such as: Facebook, YouTube, Instagram, Twitter, etc. Therefore, there is a need for a more integrated strategy using the concept of integrated marketing communications. One of the uses of social media in non-profit organizations or services based on religious beliefs is that apart from being a medium for disseminating information, it is also used to raise funds or distribute donations. Apart from the marketing communications aspect, it is recommended that LAI be able to plan marketing communications for innovative products and services based on digital media, even though traditional print media is still needed to serve Christians in remote areas.